Cifas Fraudscape 2019. Issue 7 (July 2019) - Unknown
Abstract : Based on incident reports from its members, the latest edition of this annual report from Cifas paints a dark picture of growing levels of fraud, a sharp rise in the use of money mules and increases in identity theft, especially affecting the young and old.